2016
DOI: 10.1089/ham.2016.0043
|View full text |Cite
|
Sign up to set email alerts
|

History of Migraine Predicts Headache at High Altitude

Abstract: A history of migraine is a risk factor for the development of headache at altitude and is strongly associated with the development of migrainous headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…Alcohol consumption was one of the risk factors of AMS at Mount Kinabalu. Our finding contradicts previous studies that found alcohol consumption not to be a predictor of AMS (Schneider et al, 2002 ; Mairer et al, 2010 ; Davis et al, 2016 ). Some advised against the use of alcohol at a higher altitude as alcohol inhibits acute ventilation adaptation to mild hypoxia and impairs judgment (Roeggla et al, 1995 ; Klocke et al, 1998 ; Kim et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Alcohol consumption was one of the risk factors of AMS at Mount Kinabalu. Our finding contradicts previous studies that found alcohol consumption not to be a predictor of AMS (Schneider et al, 2002 ; Mairer et al, 2010 ; Davis et al, 2016 ). Some advised against the use of alcohol at a higher altitude as alcohol inhibits acute ventilation adaptation to mild hypoxia and impairs judgment (Roeggla et al, 1995 ; Klocke et al, 1998 ; Kim et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 99%
“… 106 Some epidemiological data suggest an increased prevalence of migraine in HA populations 107 but also a worsening of both frequency and intensity of migraine episodes in low altitude residents during trekking or long flights. 108 There seems to be no difference between migraine without (M) or with aura (MA). M does not present an increased risk of developing cerebrovascular events, while in MA this risk is significantly increased even in young people with associated risk factors, such as smoking and oral contraceptive therapy.…”
Section: Literature and Research Methodsmentioning
confidence: 98%
“…14 Those patients would benefit taking daily triptans or non-steroidal anti-inflammatory drugs (NSAIDs) all through the menstrual period or during the duration of stay on high altitudes. 15 Control of other risk factors is also essential for migraine prevention e.g. weight loss and avoidance of psychological stress.…”
Section: Prevention Of Migrainementioning
confidence: 99%